AZ-ZIHAFAT FI MU’ALLAQAH ZUHAIR BIN ABI SULMA: DIRASAH ‘ARUDHIYYAH - Albar Waritsul Fuqoha (Afshaha: Jurnal Bahasa dan Sastra Arab, 2025)
Pre-Islamic poetry occupies a vital position in the corpus of Arabic literature, not only for its linguistic richness but also for its metrical structures, which later became the foundation for the development of ʿaruḍ theory. The Mu‘allaqah of Zuhair bin Abi Sulma represents one of the most prominent texts that exhibit both aesthetic refinement and rhythmic complexity, making it a worthy subject of detailed metrical investigation. This study aims to uncover and identify the forms of zihaf and its distribution across all verses of Zuhair’s Mu‘allaqah. Employing a qualitative-descriptive approach with the metrical text analysis method or ʿarudh analysis, the research examines 63 verses as the primary data source, collected through documentation techniques and processed using taqthi’ procedures to determine the wazan, the position of each tafʿilah, and the patterns of rhythmic alteration.The findings reveal that Zuhair consistently employs the bahr thawil in its classical form, with variations of tafʿilah including fa‘ulu, fa‘ulun, mafa‘ilu, mafa‘ilun, and mafa‘iilun. A total of 81 occurrences of zihaf were identified in the hasywu, most of which are qabdh applied to fa‘ulun (76 occurrences) and to mafa‘iilun (5 occurrences). Additionally, the ‘arudh appears in two forms - mafa‘ilu and mafa‘ilun - while the dharb remains consistently in the form of mafā‘ilu throughout all verses. These findings affirm that Zuhair maintains the purity of bahr thawil while applying zihaf selectively to preserve musical flexibility without disturbing rhythmic balance, thereby producing a poetic structure that is stable, dignified, and rich in moral resonance